Psychometric properties of Indonesian physics motivation questionnaire using Rasch model - Sukarelawan, Moh Irma; Ramadhan, Muhammad Firman; Oktova, Raden; Jumadi, Jumadi; Puspitasari, Ariati Dina; Indratno, Toni Kus; Nuryana, Zalik (International Journal of Evaluation and Research in Education (IJERE), 2024)
The transition to online learning during the pandemic has significantly impacted Indonesian students’ physics learning motivation. Recognizing the need for culturally relevant tools to assess this motivation, this study aims to adapt the physics motivation questionnaire (PMQ) to the Indonesian context. This research, which was conducted on 107 secondary and vocational school students, had a balanced gender distribution and used survey methodology. The PMQ, which was adapted from the biology motivation questionnaire (BMQ) through a rigorous forward-backward translation process, was analyzed for its psychometric properties using the Rasch model. This analysis focuses on the content aspects of construct validity, assessing content relevance, representativeness, and technical quality. The results show that the PMQ, using a 4-point Likert scale, effectively addresses these elements, thus confirming its reliability and applicability in the Indonesian educational environment. This study concludes that the culturally adapted PMQ is a valuable instrument for evaluating Indonesian students’ motivation to study physics, especially in the context of ongoing changes in the educational landscape.